Molecular Characterization of a Nondemyelinating Variant of Daniel’s Strain of Theiler’s Virus Isolated from a Persistently Infected Glioma Cell Line - Lin, Xiaoqi (American Society for Microbiology, 1998)
Wild-type Daniel’s strain of Theiler’s virus (wt-DA) induces a chronic demyelination in susceptible mice which is similar to multiple sclerosis. A variant of wt-DA (designated DA-P12) generated during the 12th passage of persistent infection of a G26-20 glioma cell line failed to persist and induce demyelination in SJL/J mice. To identify the determinants responsible for this change in phenotype, we sequenced the capsid coding sequence (nucleotides [nt] 2991 to 3994) and found three mutations in VP1: residues 99 (Gly to Ser), 100 (Gly to Asp), and 103 (Asn to Lys). To study the role of these mutations in neurovirulence and demyelination, we prepared a recombinant virus, DAP-1C-2A/DA, with replacement of wt-DA nt 2991 to 3994 with the corresponding region of DA-P12, and viruses with individual point mutations at VP1 residues 99(Ser), 100(Asp), and 103(Lys). DAP-1C-2A/DA and viruses with a mutation at VP1 residue 99 or 100 (but not 103) completely attenuated the ability of wt-DA to induce demyelination. Failure to induce demyelination was not due to a general failure in growth, since DA-P12 and other mutant viruses lysed L-2 cells in vitro as effectively as wt-DA. The change in disease phenotype was independent of the specific B- or T-cell immune recognition because a decrease in the neurovirulence of mutant viruses was observed in neonatal mice and immune-deficient RAG1 −/− mice. This difference in neurovirulence is not the complete explanation for the failure of DA-P12 to demyelinate, since virus with a mutation at residue 103(Lys) had decreased neurovirulence but did induce demyelination. Therefore, point mutation at VP1 residue 99 or 100 altered the ability of wt-DA to demyelinate, perhaps related to a disruption in interaction between virus and receptor on certain neural cells.